Influence of a reconstituted basement membrane and its components on casein gene expression and secretion in mouse mammary epithelial cells. - Li, M L (1987)
When primary mouse mammary epithelial cells are cultured on plastic, they rapidly lose their ability to synthesize and secrete most milk proteins even in the presence of lactogenic hormones, whereas cells cultured on released type I collagen gels show greatly enhanced mRNA levels and secretion rates of beta-casein and of some other milk proteins. We show here that culture on a reconstituted basement membrane from Engelbreth-Holm-Swarm tumor (EHS) allows greater than 90% of cells to produce high levels of beta-casein. By comparison, 30-40% of cells on released type 1 gels and only 2-10% of cells on plastic express beta-casein after 6 days in culture. Because only 40% of cells from late pregnant gland produced beta-casein before culture, the EHS matrix can both induce and maintain an increased level of casein gene expression. Individual basal lamina components were also evaluated. Type IV collagen and fibronectin had little effect on morphology and beta-casein mRNA levels. In contrast, both laminin and heparan sulfate proteoglycan increased beta-casein mRNA levels (1.5- to 4-fold and 2- to 8-fold, respectively). However, for heparan sulfate proteoglycan, increased message was not accompanied by increased secretion of beta-casein. Profound morphological differences were evident between cells cultured on plastic and on EHS matrix, the latter cells forming ducts, ductules, and lumina and resembling secretory alveoli. These results emphasize the vital role of the extracellular matrix in receiving and integrating structural and functional signals that can direct specific gene expression in differentiated tissues.